Case Report - Squamous Cell Carcinoma "Transformation" Concurrent with Secondary T790M Mutation in Resistant EGFR-Mutated Adenocarcinomas. Issue 4 (April 2016) - Jukna, Agita; Montanari, Gloria; Mengoli, Maria Cecilia; Cavazza, Alberto; Covi, Marisa; Barbieri, Fausto; Bertolini, Federica; Rossi, Giulio
ABSTRACT : N/A: The authors report two cases of epidermal growth factor receptor gene (EGFR)‐mutant stage IV lung adenocarcinomas developing immunohistochemically proven squamous cell carcinoma (SCC) "transformation" concurrently with T790M EGFR mutation, leading to acquired resistance to EGFR inhibitors. Moreover, the histologic change of EGFR‐mutant lung adenocarcinoma into SCC has been recently reported in literature. The histological transformation to SCC appears as a novel mechanism of acquired EGFR TKI resistance in EGFR‐mutated adenocarcinomas and it may be challenging for treatment.